Evaluation of the Performances and IOFCC of Broilers Fed the Whole, the Skinless, and the Skin of Leubim Fish Waste Meals Based Partial Replacement Feed of Commercial Diets - zulfan zulfan; Muhammad Daud; Cut Aida Fitri; Wenny Ultaria Munthe; Siti Zharfa Rasyiqah (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
This study aimed to evaluate the performances of broilers fed the commercial diet CP511 (CCP) partially substituted with leubim fish waste meal (LFW) processed into different parts i.e. whole leubim fish waste meal (LFWW), skinless leubim fish meal (LFM‒S), and leubim fish waste skin meal (LFWS), each mixed with yellow corn (YC) and top mix (TM). This research was conducted at the Field Laboratory of Animal Husbandry (LLP), Syiah Kuala University from March 17 to April 21, 2021. This study used 100 DOC broiler chickens strain CP 707 and commercial local fish meal (CFM). The study used a completely randomized design (CRD) consisting of 5 treatments and 4 replications. The treatment was CCP= 100% CP511 (control+) and the CCP replaced with: CFM (control-), LFWW, LFM‒S, and LFWS with the equal amount of 8% each and the addition of 8% YC + 0.5% TM each. The results showed that although statistically no significant differences (P>0.05), the inclusion of LFW meals in the form of LFWW, LFM‒S, or LFWS plus YC + TM each to substitute partially CCP tended to have higher body weight gain (BWG), final body weight (FBW), feed intake, and better feed conversion ratio (FCR), and protein efficiency ratio (PER), while protein intake (PI) significantly increased (P<0.05). The inclusion of LFW-based diets reduced feed cost and increased income over feed & chick cost (IOFCC). The LFW‒S diet did not result in better broiler performances than the LFWW diet. In conclusion, LFW meals processed as a whole, without the skin, and the only skin added with yellow corn and top mix as a partial replacement for the commercial diet increased BWG, FBW, PI, FI, and improved FCR, reduced feed cost, and generated better profit. It was suggested not to dispose of the skin out of the waste since the whole leubim fish waste meal carried out more advantages.